LEARNING DISORDER OF THE MAIN CHARACTER AS REFLECTED IN THE THEORY OF EVERYTHING MOVIE - Fadilla Oktaviana (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Nowadays, along with the times and technology, movies have become one of the most effective mass-communication media, which can be used as a place to share knowledge, tell stories, or provide certain information. One of them is to provide information about education, where during the learning process students may experience learning disorders, both students with normal physical and students with disabilities. This research aims to analyze how learning disorders occur in the main character and to analyze how the intrinsic motivation of the main character in The Theory of Everything movie. In this research used content analysis method. The object of this research is The Theory of Everything movie which describes Stephen Hawking’s life until he achieved his success. Based on the analysis that has been done, the results of the research found are: the learning disorders occur in the main character of The Theory of Everything movie is caused by amyotrophic lateral sclerosis, such as: motor disorders and communication disorders. In motor disorders, the main character has developmental coordination disorder and stereotypic movement disorder. While on communication disorders, the main character has speech sound disorder, childhood-onset fluency disorder (stuttering), and unspecified communication disorder. In addition, the intrinsic motivation of the main character can be seen from all aspects of intrinsic motivation, they are: the needs to fulfil dissatisfaction when he has not completed his task, knowing his progress, and have aspirations or goals in his life.